The Low Connection Between Informal Digital Learning of English and Willingness to Communicate: Investigating the “Scrolling Phenomenon” and Speaking Challenges among EFL Vocational Students - Nurhandayani Supraptiningsih; Ilham Sakti Aji (Journal of Pragmatics Research, 2026)
Informal Digital Learning of English (IDLE) provides extensive authentic input; however, its casual digital register often diverges from the formal sociopragmatic requirements of vocational contexts. This study investigates the impact of such informal exposure on Willingness to Communicate (WTC) among 229 vocational school students. To address self-report bias, the data were collected using a situated measurement protocol through a validated 15-item questionnaire that measured Receptive IDLE (consuming content), Productive IDLE (creating content), and WTC, following industry-specific simulations that anchored WTC in a professional rather than social context. Descriptive analysis revealed a "scrolling" phenomenon: students were highly engaged in receptive activities like watching TikTok/Instagram Reels (M = 3.08), but showed low engagement in productive activities such as online chatting (M = 2.31). Pearson correlation analysis indicated a statistically significant but weak positive correlation between Receptive IDLE and WTC (r = 0.260, p < 0.01) and a negligible correlation between Productive IDLE and WTC (r = 0.139, p < 0.05). Rather than dismissing these weak correlations as negligible, this study interprets them as empirical evidence of a pragmatic dissonance, that is, a critical gap in which informal digital pragmatic linguistic gains fail to transfer into professional sociopragmatic competence. The findings suggest that while 'scrolling' and 'posting' increase familiarity, they do not inherently build professional confidence. Therefore, it is suggested that educators bridge this dissonance through a mixed or combined pedagogical approach that integrates explicit register awareness with task-based vocational simulations to transform informal digital input into professionally competent output.